2006
DOI: 10.1530/rep.1.00976
|View full text |Cite
|
Sign up to set email alerts
|

Differential glucocorticoid effects on proliferation and invasion of human trophoblast cell lines

Abstract: Several clinical situations require continuous glucocorticoid (GC) treatment during pregnancy. A well-known deleterious side effect of such treatment is the higher incidence of growth-restricted fetuses, for which a too shallow trophoblast invasion is presently hypothesised as the underlying cause. This study investigated whether the synthetic GC triamcinolone acetonide (TA) influences proliferation, invasion and endocrine activity of human trophoblast. BeWo and JEG-3 choriocarcinoma cell lines both express GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 65 publications
2
34
0
1
Order By: Relevance
“…In another study, BeWo and JEG-3 choriocarcinoma cell lines used as models for human trophoblast were cultured with another synthetic glucocorticoid triamcinolone acetonide (TA). TA altered the number of viable and dead cells as well as cyclin B1 expression levels shown by Western blotting and to a lesser extent, invasion of BeWo and JEG-3 cell lines determined by Matrigel invasion assay and by measuring the secretion (ELISA) of matrix-metalloproteinases (MMP-2, MMP-9) [97].…”
Section: Labyrinth Zonementioning
confidence: 96%
“…In another study, BeWo and JEG-3 choriocarcinoma cell lines used as models for human trophoblast were cultured with another synthetic glucocorticoid triamcinolone acetonide (TA). TA altered the number of viable and dead cells as well as cyclin B1 expression levels shown by Western blotting and to a lesser extent, invasion of BeWo and JEG-3 cell lines determined by Matrigel invasion assay and by measuring the secretion (ELISA) of matrix-metalloproteinases (MMP-2, MMP-9) [97].…”
Section: Labyrinth Zonementioning
confidence: 96%
“…Therefore, it may be possible that the progranulin synthesized mainly in the syncytiotrophoblast in vivo stimulates the cell proliferation of the proliferating extravillous cytotrophoblast cells in a paracrine manner [20]. The reason why the effect was not observed in Jeg-3 cells is obscure, but this clearly shows the different behavior of these two cell lines, which has been observed also by other investigators [21][22][23].…”
Section: Discussionmentioning
confidence: 51%
“…The glucocorticoid re ceptor has been identified in primary trophoblast cells, as well as in the extravillous trophoblast cell line HTR-8/SVneo (20,21). It has been shown that one of the cell lines used in this study, JEG-3, expresses GR, while JAr cells were reported to lack the GR (22,23). However, an independent study has shown that some JAr cells contain low levels of GR, and therefore could be sensitive to glucocorticoid treatment (24).…”
Section: Discussionmentioning
confidence: 66%